3D hyperbranched heterostructures of Ag nanocrystals-decorated ZnO nanopillars: controlled growth and characterization of the optical properties. Issue 37 (7th September 2017) - Daud, S. N. H.; Haw, C. Y.; Chiu, W. S.; Aspanut, Z.; Jani, N. A.; Khiew, P. S.; Lim, Y. C.; Abd. Hamid, M. A.; Ali, A. M.
Abstract : Mechanistic formation of 3D hierarchical structure of silver-decorated ZnO nanopillars grown on Zn foil via a hydrothermal route. Abstract : Herein, the synthesis along with the structural and optical characterization of 3D hyperbranched ZnO nanopillars (NPLs) decorated with Ag nanocrystals (NCs) is reported. This hyperbranched heterostructure, displaying broccoli-like morphology, was prepared via two-step synthesis method, in which freestanding ZnO NPLs were hydrothermally grown onto a Zn foil substrate, followed by scrupulous decoration with Ag NCs using a similar approach. FESEM observations revealed that the reaction time highly influenced the crystallization mechanism, whereby the as-deposited Ag NCs could serve as a catalyst to induce secondary nucleation sites that promote the sprouting of secondary ZnO NPLs branches that grow along the edges of the upper half of the primary ZnO NPLs. HRTEM analysis was conducted to investigate the crystallography structure at the interfaces and elemental mapping was used to probe the elemental distribution. These results were further complemented with both XRD and Raman spectroscopy. Finally, diffuse reflectance and photoluminescence analysis were employed to elucidate the optical behaviour. A possible growth mechanism for obtaining such a unique broccoli-like morphology with a complicated nanoarchitecture is proposed. The present study could assist the development of a crystal engineering process for the preparation and analysis of hybrid nanostructures.